P.125 A severe case of Menkes: an infant's presentation with intraventricular hemorrhage. (17th June 2016) - Szelemej, PA; Stevic, I; Del Bigio, M; Mhanni, A; Hartley, J; Greenberg, C; Frosk, P; Seargeant, L
Abstract : Background: Menkes disease is a rare, X-linked recessive disorder of the ATP7A gene, a copper transporter; resulting in systemic copper deficiency. The deficient function of copper-dependent enzymes manifests clinically with failure to thrive, seizures, hypotonia, coarse hair, connective tissue abnormalities, and neurodegeneration. Cerebral arteries are often elongated, tortuous, and fragile.Methods: This case report was prepared using the patient's hospital chart, and a review of the literature undertaken using PubMed. Our case was subsequently compared and contrasted to known Menkes' literature.Results: We present the case of a 2 month old male with Menkes disease who presented with new seizure onset in the setting of a Grade III intraventricular hemorrhage with hydrocephalus. He deteriorated into status epilepticus, and palliative care was instituted. On autopsy, pronounced tortuosity of his cerebral vasculature was noted, as well as a bilaterally cystic brain with an organizing hemorrhage on the ventral surface of the brainstem.Conclusions: Although Menkes disease often presents with seizures, neurologic deterioration, and abnormal cerebral vasculature; the quick demise subsequent to an intraventricular hemorrhage is somewhat unusual and discussed.